Antimicrobial Activity of Honey with Special Reference to Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) - Guruvu Neeraja Rani; Radhika Budumuru; Narasinga Rao Bandaru (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Antimicrobial agents are essentially important in reducing the global burden of infectious diseases. With the irrational and excessive use of antibiotics in underdeveloped and developing countries, there may be chances to develop and spread resistant pathogens in the community. As a result, the effectiveness of the antibiotics is diminishing. Therefore, the need for novel alternative antimicrobial strategies has renewed interest in natural products like turmeric, honey, ginger and others exhibiting antibacterial properties. This situation has led to a re-evaluation of the therapeutic use of ancient remedies like honey as no other studies are available in the state of Andhra Pradesh with the locally available honey. Aim: To find out the efficacy of antibacterial activity of locally available honey against Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) isolates. Materials and Methods: A prospective study on the antibacterial activity of Bharat multi floral pasteurised honey which was locally available in the state of Andhra Pradesh, further it was conducted and evaluated against the bacterial strains of Methicillin Resistant Staphylococcus aureus and Methicillin Sensitive Staphylococcus aureus. Their antibacterial sensitivity pattern was tested using Kirby-Bauer disc diffusion susceptibility testing technique of CLSI along with other commonly used antimicrobials. Results: Both MRSA and MSSA isolates were sensitive to honey. But MRSA were resistant to all antimicrobials tested except linezolid where as MSSA were sensitive to all except penicillin. Conclusion: It is definitely worthy to consider honey as a promising future antimicrobial to be tested and studied. Honey, may be elaborately used in future with some more molecular studies on its method of action as an antimicrobial agent.